Whole genome sequencing of foodborne pathogens and global data sharing development - Xiaoran LI; Ruohong ZHANG; Yang YANG; Shenghui CUI; Yunchang GUO (Zhongguo shipin weisheng zazhi, 2020)
With the rapid development of molecular typing techniques for monitoring foodborne pathogens and outbreak investigations, whole genome sequencing (WGS) is gradually revealing its importance. In the context of the globalization of food trade, it’s urgent to establish details of the links between foodborne pathogens and human exposure in order to accurately monitor and reduce their occurrence. The accuracy of WGS is significantly better than prior analysis tools in the aspect. In this paper, we take Listeria monocytogenes as example to expound the monitoring of foodborne pathogens and the investigation of infection outbreaks, emphasizing the value of WGS in trace-back of foodborne diseases. The technologies for data generation and analysis are summarized, the practical application progress of WGS in the worldwide foodborne pathogen typing is emphasized, and the challenges in the future are prospected.